Funkcional'na asimetrija u sporti: osoblivosti projavu ta p?dhodi do vikoristannja v procesi orientacii pidgotovki fehtuval'nikiv - Ulan, A.; Shynkaruk, O. (Science in Olympic Sport, 2019)
Objective. To study the functional asymmetry in fencing, to substantiate the approach to the orientation of the training of athletes taking into account the individual profiles of functional asymmetry. Methods. Analysis of literature and materials of the Internet network, protocols of competitions, expert survey testing, instrumental Methods: system "OptoJump", software package "Visual 3D". 54 international and 9 all-Ukrainian competitions were analyzed. The sample size was 2515 athletes. Results. One of the manifestations of functional asymmetry in fencing is the advantage of fighting with the right or left hand and the choice of the athlete of the battle stand. Among the 1200 surveyed swordsmen (50 top in the world rankings) up to 40 % fence with their left hand. 45 % of left-handed athletes rank in the world ranking from 1 to 10 places. 17 individual profiles of functional asymmetry have been identified. Are grounded approaches of accounting of functional asymmetry for orientation of sports training: smoothing, accentuation, formation of cross-asymmetry, retraining or not taking into account asymmetry. For fencers is proposed the approach of accounting for functional asymmetry with its accentuation and redistribution of load on the unknown side, the formation of cross-asymmetry. Is developed the algorithm of orientation of training of young athletes with the account of functional asymmetry and are systematized general and special tests for its definition in initial stages of long-term preparation. Conclusion. The individual profi le of asymmetry forms the basis of the personality of the motor activity of the swordsman and regulates his age formation, which allows him to be considered in the process of orientation of the training of beginners.